2020
DOI: 10.1088/1361-6471/ab8e94
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural networks for direct detection of dark matter

Abstract: The XENON1T experiment uses a time projection chamber (TPC) with liquid Xenon to search for Weakly Interacting Massive Particles (WIMPs), a proposed Dark Matter particle, via direct detection. As this experiment relies on capturing rare events, the focus is on achieving a high recall of WIMP events. Hence the ability to distinguish between WIMP and the background is extremely important. To accomplish this, we suggest using Convolutional Neural Networks (CNNs); a Machine Learning procedure mainly used in image … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…CNNs are showing promising potential for image based data sets for various applications in HEP see e.g. [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…CNNs are showing promising potential for image based data sets for various applications in HEP see e.g. [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…We note, however, that on an event-by-event basis, the fundamental detector response to a NR vs ER is different, and therefore supervised classification techniques can be used to discriminate between signal and background, as was observed in Ref. [43]. A key result we found whilst validating the results of this study was that such supervised methods work exceptionally well for background rejection regardless of the DM mass and cross-section as well, since the fundamental property being learned by the model is the NR and ER detector response.…”
Section: A Model Independence and Supervised Classificationmentioning
confidence: 87%
“…Interestingly, in Ref. [34] a convolution neural network was applied to XENON1T TPC detector response images of WIMP signal events (nuclear recoils) and background events (electron recoils) achieving a classification accuracy of above 90%. In this study, we exploit a pre-trained convolutional neural network with a similar architecture to boost the anomaly awareness of our unsupervised model.…”
Section: Introductionmentioning
confidence: 99%
“…Modern deep learning methods are being increasingly applied for event reconstruction in neutrino experiments such as MicroBooNE [3,4] and DUNE [5,6]. Moreover, studies based on convolution neural networks (CNNs) are also found for dual-phase TPC-based experiments, for example, the EXO-200 [7], the XENONnNT [8], and the DarkSide-50 [9] collaborations. In addition to these, several applications of various neural network techniques were demonstrated for the LUX xenon TPC [10], not covering direct XY vertex reconstruction.…”
Section: Dual-phase Tpcs Electroluminescence and Position Reconstructionmentioning
confidence: 99%